2016
DOI: 10.1074/jbc.m115.688457
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic and Kinetic Properties of the Molybdenum-containing, NAD+-dependent Formate Dehydrogenase from Ralstonia eutropha

Abstract: We have examined the rapid reaction kinetics and spectroscopicpropertiesofthemolybdenum-containing,NAD ؉ -dependent FdsABG formate dehydrogenase from Ralstonia eutropha. We confirm previous steady-state studies of the enzyme and extend its characterization to a rapid kinetic study of the reductive half-reaction (the reaction of formate with oxidized enzyme). We have also characterized the electron paramagnetic resonance signal of the molybdenum center in its Mo V state and demonstrated the direct transfer of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
150
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(177 citation statements)
references
References 35 publications
25
150
0
2
Order By: Relevance
“…This chemical strategy -direct hydride transfer-was also recently suggested by Niks et al 32 The carbon dioxide reduction is suggested to follow the reverse reaction mechanism (Fig. 6.A, red arrows).…”
Section: Reaction Mechanismsupporting
confidence: 70%
See 1 more Smart Citation
“…This chemical strategy -direct hydride transfer-was also recently suggested by Niks et al 32 The carbon dioxide reduction is suggested to follow the reverse reaction mechanism (Fig. 6.A, red arrows).…”
Section: Reaction Mechanismsupporting
confidence: 70%
“…32 In this novel proposal, the focus is shifted from the selenocysteine and turned into the sulfo group of the active site, with the formate oxidation/carbon dioxide reduction occurring via hydride transfer (eq. 3, not eq.…”
Section: A New Look At the Reaction Mechanism Of Fdhmentioning
confidence: 99%
“…The results shown here are supported by previous results obtained in the crystal structure of E. coli FdhF, which showed that in the reduced state with formate the cysteine ligand was displaced from the active site (5). Further, the mechanism is consistent with the ones proposed by Cerqueira and coworkers by theoretical studies (14,(23)(24)(25), but is inconsistent with a recent report by Nicks et al (26), which proposed formate binding only in the second Mo coordination sphere by studies on…”
Section: Nitrate Reductase Activity Of Fdhsupporting
confidence: 50%
“…It is thus likely that the decrease in activity above pH 7.0 as described by pK a2 eff was principally due to ionic strength effects rather than ionization phenomena. The identity of the ionizable group whose protonation results in loss of activity at low pH is not known, although a likely candidate is the Mo(VI)ϭS group of the molybdenum center, which is known to be protonated at pH 7.0 upon reduction of the molybdenum (11).…”
Section: Ph Dependence Of the Reverse Reactionmentioning
confidence: 99%
“…C. necator (formerly known as R. eutropha) strain HF210 was grown as described previously (11). All protein purification steps were performed at 0 -4°C with an Ä KTA FPLC system (GE Healthcare) in a procedure modified from that of Niks et al (11).…”
Section: Protein Preparationmentioning
confidence: 99%